The influence of body weight on chosen physiological parameters in wrestling - Karnincic, H.; Krstulovic, S.; Baic, M. (Journal of Human Kinetics, 2013)
In this study, the authors attempted to determine whether the dynamics of blood lactate and glucose in wrestling depend on the weight class. Blood lactate and glucose curves during and after a wrestling match were determined. We also explained the dynamics of blood lactate and glucose in the context of recent glucose and lactate metabolism research. A sample of 60 youth wrestlers (15-20 years) were divided into three weight groups. Each athlete participated in one wrestling match. During the fight, the athletes' heart rate, glucose, and blood lactate were measured. The differences in body mass between the athletes did not affect the dynamics of lactate and glucose in wrestling competition (Fisher LSD test). We established that lactate and glucose dynamics are the same for all weight groups (Fisher LSD-Lactate 1 < 2 < 3 = 4 > 5, Fisher LSD-Glucose 1 = 2 < 3 < 4 < 5). Understanding lactate and glucose metabolism in wrestling is important for wrestling coaches because they need to evaluate a wrestler's anaerobic energy status.